Trends in survival among extremely-low-birth-weight infants (less than 1000 g) without significant bronchopulmonary dysplasia - Botet Francesc; Figueras-Aloy Josep; Miracle-Echegoyen Xavier; Rodríguez-Miguélez José; Salvia-Roiges MªDolors; Carbonell-Estrany Xavier (BMC, 2012)
Abstract Objective The aim of this study was to analyze the evolution from 1997 to 2009 of survival without significant (moderate and severe) bronchopulmonary dysplasia (SWsBPD) in extremely-low-birth-weight (ELBW) infants and to determine the influence of changes in resuscitation, nutrition and mechanical ventilation on the survival rate. Study design In this study, 415 premature infants with birth weights below 1000 g (ELBW) were divided into three chronological subgroups: 1997 to 2000 (n = 65), 2001 to 2005 (n = 178) and 2006 to 2009 (n = 172). Between 1997 and 2000, respiratory resuscitation in the delivery room was performed via a bag and mask (Ambu®, Ballerup, Sweden) with 40-50% oxygen. If this procedure was not effective, oral endotracheal intubation was always performed. Pulse oximetry was never used. Starting on January 1, 2001, a change in the delivery room respiratory policy was established for ELBW infants. Oxygenation and heart rate were monitored using a pulse oximeter (Nellcor®) attached to the newborn's right hand. If resuscitation was required, ventilation was performed using a face mask, and intermittent positive pressure was controlled via a ventilator (Babylog2, Drägger). In 2001, a policy of aggressive nutrition was also initiated with the early provision of parenteral amino acids. We used standardized parenteral nutrition to feed ELBW infants during the first 12-24 hours of life. Lipids were given on the first day. The glucose concentration administered was increased by 1 mg/kg/minute each day until levels reached 8 mg/kg/minute. Enteral nutrition was started with trophic feeding of milk. In 2006, volume guarantee treatment was instituted and administered together with synchronized intermittent mandatory ventilation (SIMV + VG). The complications of prematurity were treated similarly throughout the study period. Patent ductus arteriosus was only treated when hemodynamically significant. Surgical closure of the patent ductus arteriosus was performed when two courses of indomethacin or ibuprofen were not sufficient to close it. Mild BPD were defined by a supplemental oxygen requirement at 28 days of life and moderate BPD if breathing room air or a need for <30% oxygen at 36 weeks postmenstrual age or discharge from the NICU, whichever came first. Severe BPD was defined by a supplemental oxygen requirement at 28 days of life and a need for greater than or equal to 30% oxygen use and/or positive pressure support (IPPV or nCPAP) at 36 weeks postmenstrual age or discharge, whichever came first. Moderate and severe BPD have been considered together as "significant BPD". The goal of pulse oximetry was to maintain a hemoglobin saturation of between 88% and 93%. Patients were considered to not need oxygen supplementation when it could be permanently withdrawn. The distribution of the variables was not normal based on a Kolmogorov-Smirnov test (p < 0.05 in all cases). Therefore, quantitative variables were expressed as the median and interquartile range (IQR; 25th-75th percentile). Statistical analysis of the data was performed using nonparametric techniques (Kruskal-Wallis test and Mann-Whitney U test). A chi-square analysis was used to analyze qualitative variables. Potential confounding variables were those possibly related to BPD in survivors (p between 0.05 and 0.3 in univariate analysis). Logistic regression analysis was performed with variables related to BPD in survivors (p < 0.05) and potential confounding variables. The forward stepwise method adjusted for confounding factors was used to select the variables, and the enter method using selected variables was used to obtain the odds ratios. Results and conclusion There was an increase in the rate of SWsBPD (1997 to 2000: 58.5%; 2001 to 2005: 74.2%; and 2006 to 2009: 75.0%; p = 0.032). In survivors, the occurrence of significant BPD decreased after 2001 (9.5% vs. 2.3%; p = 0.013). The factors associated with improved SWsBPD were delivery by caesarean section, a reduced endotracheal intubation rate and a reduced duration of mechanical ventilation.While the mortality of ELBW infants has not changed since 2001, the frequency of SWsBPD has significantly increased (75.0%) in association with increased caesarean sections and reductions in the endotracheal intubation rate, as well as the duration of mechanical ventilation.